A method for preparing catalytic cracking catalyst without ammonia nitrogen pollution

Through the catalyst preparation method without ammonia nitrogen pollution, including ion exchange modification and ease of hydrothermal ultra-stable modification, combined with SiCl4 gas phase superstable modification, the problem of ammonia nitrogen pollution and long process during the catalyst preparation process is solved, and high activity and Stable catalysts improve heavy oil conversion capacity and coke selectivity.

CN115634710BActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202110817837.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-07-20
Publication Date
2025-01-07
Estimated Expiration
2041-07-20

AI Technical Summary

Technical Problem

During the preparation of existing catalytic cracking catalysts, there are problems such as ammonia nitrogen pollution, high water consumption, long process and insufficient utilization of secondary pore structures, and it is not possible to effectively obtain superstable Y-type molecular sieve catalysts with good performance.

Method used

The catalyst preparation method is adopted without ammonia nitrogen pollution, including the preparation of catalyst microspheres, ion exchange modification, hydrothermal ultra-stable modification and SiCl4 gas phase ultra-stable modification, ion exchange is carried out through rare earth solution contact to alleviate hydrothermal ultra-stable modification The treatment is carried out and reacted with SiCl4 gas to optimize the structure and performance of the finished catalyst product.

Benefits of technology

The high activity and stability of the catalyst are achieved, the pore volume and specific surface area are improved, the heavy oil conversion capacity and coke selectivity are enhanced, the sodium oxide content is reduced, the ammonia nitrogen pollution problem is solved, and the production efficiency and cost-effectiveness are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003170825250000091
    Figure BDA0003170825250000091
  • Figure BDA0003170825250000092
    Figure BDA0003170825250000092
Patent Text Reader

Abstract

The present invention relates to a method for preparing a catalytic cracking catalyst without ammonia nitrogen pollution, which comprises mixing an unmodified NaY molecular sieve with a binder, clay and water, beating and spray drying, and calcining to obtain catalyst microspheres; then, performing ion exchange modification, moderate hydrothermal ultra-stable modification and SiCl4 gas phase ultra-stable modification. The preparation method is a method for preparing a catalytic cracking catalyst without ammonia nitrogen pollution. The method can not only prepare a catalytic cracking catalyst with larger pore volume and specific surface area, better strength, stronger heavy oil conversion ability and good coke selectivity, but also, there is no ammonia nitrogen pollution in the whole process of catalyst preparation, which effectively solves the ammonia nitrogen pollution problem that needs to be solved in the production of catalytic cracking catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalytic cracking catalyst used in petroleum processing and a preparation method thereof. Background Art

[0002] In the production of catalytic cracking catalysts, the preparation process of traditional zeolite-containing catalytic cracking catalysts can be roughly divided into two categories: one is a molecular sieve first modification process, that is, the zeolite is first subjected to ultra-stable modification or ion exchange modification to prepare a molecular sieve finished product slurry, and then mixed with kaolin and a binder to prepare a catalyst colloid, which is then spray-dried and formed, and then subsequent roasting, washing, exchange and airflow drying are carried out to prepare a catalyst product; the other is a molecular sieve post-modification process, that is, the unmodified NaY zeolite is directly mixed with kaolin and a binder to prepare a catalyst colloid, which is then spray-dried and formed, and then subsequent roasting, washing, ion exchange modification and airflow drying are carried out to prepare a catalyst product.

[0003] In the catalytic cracking catalyst for producing gasoline by catalytic cracking, Y-type molecular sieve is usually used. Since the original synthesized Y-type molecular sieve is usually synthesized in the presence of a base, it contains a large amount of sodium ions. Sodium ions have many adverse effects on the reaction and the catalyst under the reaction conditions of catalytic cracking. Therefore, for the catalytic cracking reaction, it is usually hoped that the sodium content in the Y-type molecular sieve is as low as possible so that the catalytic cracking catalyst has good catalytic cracking reaction activity, stability and selectivity. However, in the prior art, the method of reducing sodium ions is usually ion exchange, and the commonly used exchange ions are such as rare earth, ammonium ions, and hydrogen ions. However, the exchange of metal ions or hydrogen ions often cannot reduce the sodium ions to the ideal content. Therefore, ammonium ions are often used for exchange in the prior art.

[0004] CN1098130A proposes a cracking catalyst and its preparation method. The catalyst is composed of 20-80m% clay, 5-40m% composite aluminum-based binder, 0-5m% oxides selected from elements such as Sn, Ti, Mg, and 5-40m% selected from faujasite, ZSM-5 zeolite, beta zeolite and mixtures thereof with a unit cell constant of 2.432-2.472nm. The preparation method is to mix clay with deionized water for pulping, add hydrochloric acid for acidification, add pseudo-boehmite, aluminum sol, zeolite molecular sieve for pulping, and obtain the product by spray drying, washing or roasting. The characteristic is that the faujasite with a unit cell constant of 2.432-2.472nm refers to REY, REHY, USY, REUSY and various Y zeolites with high silicon-aluminum ratio. These zeolites are firstly modified by ultra-stable modification or ion exchange modification.

[0005] CN1246515A discloses a method for preparing a cracking catalyst, which includes mixing molecular sieve slurry, aluminum sol, pseudo-boehmite, clay and inorganic acid to make a catalyst slurry, and then spray drying; after that, the spray-dried catalyst microspheres are sequentially roasted, washed and air-dried to obtain a finished catalyst product. It is characterized in that the molecular sieve is added before the clay and the inorganic acid, and the inorganic acid is added after the aluminum sol. Preferably, the inorganic acid is added after the aluminum sol and the pseudo-boehmite, and there is no special restriction on the order of adding the remaining materials. The invention provides a method for preparing a semi-synthetic composite aluminum-based catalytic cracking catalyst with a high solid content. Compared with the method for preparing a semi-synthetic composite aluminum-based catalytic cracking catalyst with a conventional solid content, the solid content of the catalyst slurry before spray drying can be greatly increased, the gelling time can be shortened, thereby improving the production efficiency of the catalyst, and reducing energy consumption and production costs. The molecular sieves used in this patent are all molecular sieves that have been previously modified by ultra-stable modification or ion exchange. In the ion modification process, rare earth or ammonium salts are generally used as exchange media. In the subsequent catalyst washing process, ammonium salts are still needed as exchange media to reduce the sodium content in the catalyst.

[0006] The catalytic cracking catalyst preparation method provided in this patent application has the following problems: (1) ammonium salts and a large amount of water are required in both the molecular sieve modification and the post-washing modification of the catalyst, resulting in ammonia nitrogen emission pollution and high water consumption; (2) the molecular sieve is first subjected to ultra-stable modification and ion exchange modification, and then the catalyst is prepared using the slurry of the modified molecular sieve, which results in a long process; (3) the secondary pores formed in the molecular sieve during the ultra-stable modification process are easily blocked by the aluminum sol binder used in the subsequent catalyst preparation, resulting in the secondary pore structure being unable to be effectively utilized.

[0007] CN101670295A discloses a method for preparing a cracking catalyst, including the steps of mixing a Y-type molecular sieve with a matrix, beating, and spray drying, characterized in that the Y-type molecular sieve is a NaY molecular sieve, and also includes the steps of contacting the catalyst powder obtained by spray drying with a solid salt containing exchange ions for ion exchange, washing, and drying. The catalyst powder is contacted with the solid salt containing exchange ions for ion exchange once or multiple times, and the contact temperature is 120-300°C. After each exchange, it is washed, dried or not dried; the exchange ions are ammonium ions and / or rare earth ions; the NaY molecular sieve is crystallized and synthesized, and the mother liquor is removed, and it is directly used to prepare a catalyst or washed and mixed with a matrix to prepare a catalyst. The catalyst preparation method can be used to prepare a catalytic cracking catalyst containing a Y-type molecular sieve, such as a cracking catalyst containing REY, REHY, HY or an element-modified Y molecular sieve, and is particularly suitable for preparing a cracking catalyst containing a REY molecular sieve. This method cannot obtain a catalytic cracking catalyst containing an ultra-stable Y-type molecular sieve.

[0008] CN102806096A discloses a method for preparing a rare earth-containing Y-type molecular sieve cracking catalyst, the method comprising: (1) mixing a NaY molecular sieve that has not been ion-exchanged with a matrix, slurrying and spray-drying to form a catalyst precursor; (2) subjecting the catalyst precursor to a first calcination at a temperature of 200° C. to less than 400° C., and subjecting the product obtained after the first calcination to an ammonium ion exchange; and (3) subjecting the product obtained after the ammonium ion exchange to at least one second calcination and at least one rare earth ion exchange, wherein the rare earth ion exchange is performed after the second calcination; the temperature of the ammonium ion exchange is higher than the temperature of the rare earth ion exchange; and the temperature of the second calcination is higher than the temperature of the first calcination.

[0009] In the above literature, the catalyst is directly prepared by using unmodified NaY type molecular sieve, and then modified by ammonium and / or rare earth ion exchange. However, the catalyst prepared in this way has poor coke selectivity and low activity stability in the catalytic cracking reaction of heavy oil, and it is impossible to obtain a catalytic cracking catalyst containing ultra-stable Y type molecular sieve with good performance. Summary of the invention

[0010] The technical problem to be solved by the present invention is to provide a new method for preparing a cracking catalyst containing an ultra-stable Y-type molecular sieve, which has no ammonia nitrogen pollution during the preparation process and has high activity stability, in view of the shortcomings of the existing direct preparation of catalysts using unmodified NaY-type molecular sieves.

[0011] The present invention provides a method for preparing a catalytic cracking catalyst without ammonia nitrogen pollution, which comprises sequentially preparing catalyst microspheres, ion exchange modification, mild hydrothermal ultrastable modification and SiCl4 gas phase ultrastable modification, wherein:

[0012] (1) The preparation of catalyst microspheres: unmodified NaY molecular sieve is mixed with a binder, clay and water, beaten and spray-dried to form, and calcined in a calcining furnace at 280-380° C. for 1-4 hours to obtain catalyst microspheres A; wherein, on a dry basis, the weight ratio of the binder to the unmodified NaY molecular sieve is 10-45:10-50, and the weight ratio of the clay to the unmodified NaY molecular sieve is 10-80:10-50, for example, 20-60:15-50;

[0013] (2) Ion exchange modification: the catalyst microspheres A are contacted with a rare earth solution to carry out an ion exchange reaction, filtered, and washed to obtain catalyst microspheres B containing rare earth with reduced sodium oxide content; wherein the rare earth solution is also called a rare earth salt solution;

[0014] (3) The moderate hydrothermal ultrastable modification: The catalyst microspheres B are subjected to a moderate hydrothermal ultrastable modification treatment, and optionally dried to obtain catalyst microspheres C, wherein the moderate hydrothermal ultrastable modification treatment is to calcine the catalyst microspheres B at a temperature of 350 to 450° C. in an atmosphere containing 40 to 60% by volume of water vapor (also referred to as a 40 to 60% by volume water vapor atmosphere or 40 to 60% water vapor) for 4 to 6 hours;

[0015] (4) The SiCl4 gas phase ultra-stable modification: the catalyst microspheres C are contacted with SiCl4 gas at a temperature of 250-450°C for reaction, wherein the weight ratio of SiCl4 to catalyst microspheres C on a dry basis is 0.03-0.2:1, the reaction time is 10 minutes to 5 hours, and then washed, filtered, optionally dried, and optionally calcined to obtain a catalyst product D. The water content of the catalyst microspheres C is preferably not more than 1% by weight; if the water content of the catalyst microspheres C obtained in step (3) is not more than 1% by weight, it can be directly used for contact with silicon tetrachloride to carry out the reaction; if the water content of the catalyst microspheres C obtained in (3) exceeds 1% by weight, the catalyst microspheres C are dried to make their water content less than 1% by weight.

[0016] In the method for preparing a catalytic cracking catalyst provided by the present invention, based on the dry weight of catalyst microspheres A, the catalyst microspheres A contain 10 to 50 weight percent of unmodified NaY molecular sieve, 10 to 40 weight percent of a binder and 10 to 80 weight percent of clay on a dry basis.

[0017] In the method for preparing the catalytic cracking catalyst provided by the present invention, the catalyst microsphere A may also contain other molecular sieves other than the unmodified NaY type molecular sieve, and the content of the other molecular sieves on a dry basis is, for example, 0 to 40% by weight, for example, 0 to 30% by weight or 1 to 20% by weight, based on the weight of the catalyst. The other molecular sieves are molecular sieves used in the autocatalytic cracking catalyst, for example, one or more of zeolites with MFI structure such as HZSM-5, ZRP, and ZSP, the Beta zeolite such as Hβ, the non-zeolite molecular sieves such as aluminum phosphate molecular sieve (AlPO molecular sieve), silicon aluminum phosphorus molecular sieve (SAPO molecular sieve) One or more.

[0018] The present invention provides a method for preparing a catalytic cracking catalyst, wherein the content of the unmodified NaY molecular sieve in the catalyst microsphere A is 10 to 50% by weight, preferably 15 to 45% by weight, for example 25 to 40% by weight, on a dry basis. The unmodified NaY molecular sieve refers to the original synthesized NaY molecular sieve that has not been modified in other ways except for washing with water, for example, the unmodified NaY molecular sieve is a hydrothermally synthesized NaY molecular sieve that has only been washed with industrial water and the pH of the filter cake of the NaY molecular sieve after washing is 7.0 to 9.0, preferably 7.0 to 8.0. The hydrothermally synthesized NaY molecular sieve can be purchased commercially or synthesized with reference to the prior art, for example, with reference to the method provided in the claims or examples of U.S. Patents US3639099 and US3671191.

[0019] In the method for preparing a catalytic cracking catalyst provided by the present invention, the clay is selected from one or more clays used as cracking catalyst components, such as kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, saponite, rectorite, sepiolite, attapulgite, hydrotalcite, and bentonite. These clays are well known to those of ordinary skill in the art. Preferably, the content of the clay in the catalytic cracking catalyst provided by the present invention is 20 to 55% by weight or 30 to 50% by weight on a dry basis.

[0020] In the method for preparing a catalytic cracking catalyst provided by the present invention, the binder is one or more of a silicon-based binder, an aluminum-based binder, a zirconium-based binder or a silicon-aluminum binder. The silicon-based binder is, for example, silica sol; the aluminum-based binder is, for example, one or more of alumina sol, pseudo-boehmite, and alumina gel; the zirconium-based binder is, for example, zirconium sol; the silicon-aluminum binder is, for example, silicon-alumina sol or silicon-alumina gel.

[0021] In the method for preparing a catalytic cracking catalyst provided by the present invention, in one embodiment, the binder is an aluminum-based binder or an alumina binder, and the content of the alumina binder in the catalyst microsphere A is 10 to 40% by weight, for example, 20 to 35% by weight, calculated on a dry basis. The alumina binder of the present invention is selected from one or more of various forms of alumina, hydrated alumina and alumina sol commonly used in cracking catalysts. For example, the alumina binder is selected from one or more of γ-alumina, η-alumina, θ-alumina, χ-alumina, pseudoboemite, Boehmite, gibbsite, Bayerite or alumina sol. Calculated on a dry basis, the weight ratio of the alumina binder to the unmodified NaY molecular sieve is 10-40:10-50, for example, 15-35:20-45, preferably 20-30:25-40. The alumina binder is preferably pseudo-boehmite and aluminum sol. For example, the catalytic cracking catalyst contains 2-15 wt. %, preferably 3-10 wt. % of aluminum sol based on alumina, and 10-30 wt. %, preferably 15-25 wt. % of pseudo-boehmite based on alumina.

[0022] When the binder is an aluminum-based binder, preferably aluminum-based binders are aluminum sol and pseudo-boehmite, the slurry is prepared by slurrying clay such as kaolin and / or other clays with aluminum sol; slurrying alumina and / or alumina precursor such as pseudo-boehmite with hydrochloric acid, preferably with an acid-aluminum ratio of 0.10 to 0.30 (molar ratio of acid to pseudo-boehmite calculated as aluminum oxide); then mixing the two slurries and slurrying with unmodified NaY molecular sieve or unmodified NaY molecular sieve slurry to obtain a catalyst colloid. The solid content of the catalyst colloid is preferably 28 to 40% by weight.

[0023] The method for preparing a catalytic cracking catalyst provided by the present invention can be operated without heating and aging by using an aluminum-based binder. No heating during the mixing and beating process is beneficial to reducing energy consumption, and can also avoid the high viscosity of the slurry that cannot be transported due to heating, which is beneficial to increasing the solid content of the slurry, thereby helping to reduce production costs and improve production efficiency. In one embodiment, the mixing and beating is to mix the unmodified NaY molecular sieve with an alumina binder, clay and water at ambient temperature, such as room temperature (room temperature 15-40°C), and then stir for more than 30 minutes, such as 30-180 minutes or 30-60 minutes for beating, and the mixing and beating process can be performed without heating and aging.

[0024] In one embodiment, the binder is a silicon-based binder, such as one or more of silica gel and silica sol, preferably silica sol, such as acidic silica sol, alkaline silica sol or neutral silica sol. The weight ratio of silica sol to unmodified NaY molecular sieve on a dry basis is 5-45:10-50, such as 15-30:20-50. Preferably, when silica sol is contained, a pseudo-boehmite binder is also used, and the weight ratio of the pseudo-boehmite binder on a dry basis to the silica sol on a dry basis is 0.1 to 1:1.

[0025] According to the method provided by the present invention, the method of mixing and slurrying the unmodified NaY molecular sieve with the binder, clay and water has no special requirements compared with the existing catalytic cracking catalyst preparation method. The solid content of the obtained slurry is preferably 28 to 40% by weight.

[0026] In the method for preparing a catalytic cracking catalyst provided by the present invention, the calcination temperature for preparing the catalyst microspheres A in step (1) is preferably 280-380° C., such as 300-350° C. The calcination time is 1-4 hours, such as 2-3 hours.

[0027] According to the method for preparing catalytic cracking catalyst provided by the present invention, there is no special requirement for the spray drying method, and it can be carried out according to the spray drying method in the existing cracking catalyst preparation process.

[0028] In the method for preparing a catalytic cracking catalyst provided by the present invention, the temperature of the ion exchange reaction in step (2) (also referred to as the exchange temperature) is 20 to 60° C., preferably 25 to 45° C., the exchange time is 90 to 120 minutes, and the rare earth solution is an aqueous solution of a rare earth salt; the rare earth salt is preferably rare earth chloride and / or rare earth nitrate.

[0029] In one embodiment, the concentration of the rare earth salt solution is 200-350 g / L in terms of RE2O3, and the weight ratio of the rare earth solution to the catalyst microspheres A is preferably 0.03-0.3.

[0030] The sodium oxide content in the catalyst microspheres B is preferably 1.5 to 2.5% by weight.

[0031] Preferably, the ion exchange is performed so that the rare earth content in the obtained catalytic cracking catalyst is preferably 1 to 4% by weight as calculated as RE2O3.

[0032] In the method for preparing the catalytic cracking catalyst provided by the present invention, the temperature of the mild hydrothermal ultrastable modification treatment is 350-450°C, preferably 370-420°C.

[0033] In the catalytic cracking catalyst provided by the present invention, the moderate hydrothermal ultrastable modification treatment atmosphere is an atmosphere containing 40 to 60% by volume of water vapor, preferably an atmosphere containing 45 to 55% by volume of water vapor. Other gases in the atmosphere may be, for example, one or more of air, nitrogen, and helium.

[0034] In the method for preparing the catalytic cracking catalyst provided by the present invention, the mild hydrothermal ultrastable modification treatment time is 4 to 6 hours, preferably 5 to 6 hours.

[0035] In the method for preparing the catalytic cracking catalyst provided by the present invention, the temperature for the contact reaction between the catalyst microspheres C and the SiCl4 gas is 250-450°C, preferably 280-420°C.

[0036] In the method for preparing a catalytic cracking catalyst provided by the present invention, the time (reaction time) for the catalyst microspheres C to contact and react with SiCl4 gas is 10 minutes to 5 hours, for example, 0.2-2 hours, preferably 30 minutes to 2 hours.

[0037] In the method for preparing a catalytic cracking catalyst provided by the present invention, the weight ratio of the reaction materials in the contact reaction between the catalyst microspheres C and SiCl4 gas is SiCl4:catalyst microspheres C = 0.05-0.2:1, and preferably SiCl4:catalyst microspheres = 0.07-0.15:1.

[0038] In the method for preparing a catalytic cracking catalyst provided by the present invention, the washing method described in step (4) is preferably washing with water. In one embodiment, the washing conditions are catalyst: H2O=1:8-12, the pH value is preferably 3.0-4.0, and the washing temperature is 20-50° C. The water can be acidic water such as decationized water.

[0039] The drying in step (4) can be drying or airflow drying. The calcination temperature can be 400-600°C and the calcination time can be 0.5-5 hours.

[0040] Preferably, the sodium oxide content in the obtained catalytic cracking catalyst does not exceed 0.15% by weight.

[0041] The method for preparing a catalytic cracking catalyst provided by the present invention has no ammonia nitrogen pollution during the preparation process, and can obtain a catalytic cracking catalyst with a lower sodium oxide content, effectively solving the ammonia nitrogen pollution problem that needs to be solved in the production of catalytic cracking catalysts. The method for preparing a catalyst provided by the present invention can obtain a catalytic cracking catalyst containing an ultra-stable Y-type molecular sieve with excellent performance, which has high activity and high activity stability. Compared with catalysts with the same or similar compositions, the catalytic cracking catalyst obtained by the method provided by the present invention has a larger pore volume and a larger specific surface area. Surprisingly, the obtained catalyst has a stronger heavy oil conversion ability and better coke selectivity, and has a higher gasoline yield when used for heavy oil cracking, and has high activity stability. DETAILED DESCRIPTION

[0042] The present invention will be further described in the following examples, but the present invention is not limited thereto.

[0043] In the embodiments and comparative examples, the unmodified NaY molecular sieve (also called NaY zeolite) is provided by Qilu Branch of Sinopec Catalyst Co., Ltd., with a sodium oxide content of 13.5% by weight, a framework silicon-aluminum ratio (SiO2 / Al2O3 molar ratio) of 4.6, a unit cell constant of 2.470nm, and a relative crystallinity of 90%. It is the original synthesized NaY molecular sieve washed with industrial water and the pH value of the filter cake after washing is 7.6; rare earth chloride and rare earth nitrate are chemically pure reagents produced by Beijing Chemical Plant. Pseudo-boehmite is an industrial product produced by Shandong Aluminum Plant, with a solid content of 61% by weight; kaolin is a special kaolin for cracking catalyst produced by Suzhou China Kaolin Company, with a solid content of 76% by weight; aluminum sol is provided by Qilu Branch of Sinopec Catalyst Co., Ltd.; silica sol is provided by Qilu Branch of Sinopec Catalyst Co., Ltd., wherein the silicon oxide content is 25% by weight and the pH value is 2.5.

[0044] Analysis method: In each comparative example and embodiment, the element content of the catalyst is determined by X-ray fluorescence spectroscopy; the unit cell constant and relative crystallinity of the zeolite in the catalyst are determined by X-ray powder diffraction (XRD) using RIPP145-90 and RIPP146-90 standard methods (see "Petrochemical Analysis Methods" (RIPP Test Methods), edited by Yang Cuiding et al., Science Press, published in 1990). The specific surface area of ​​the catalyst is detected using the Autosorb-1 nitrogen adsorption and desorption instrument of the American Quanta Corporation according to the GB / T5816-1995 method, and the sample needs to be degassed at 300°C for 6 hours before the test. The total pore volume of the catalyst is detected according to the RIPP151-90 standard method (see "Petrochemical Analysis Methods >> (RIPP Test Methods), edited by Yang Cuiding et al., Science Press, published in 1990). According to the RIPP29-90 standard method (see "Petrochemical Analysis Methods >> (RIPP Test Methods), edited by Yang Cuiding et al., Science Press, published in 1990), the wear index of the catalyst (used to characterize the wear resistance, the smaller the wear index, the better the wear resistance) is tested.

[0045] Unless otherwise specified, the chemical reagents used in the comparative examples and embodiments are of chemically pure quality.

[0046] Example 1

[0047] (1) 166 kg of decationized water was added to the catalyst gelling kettle, and then the gelling raw materials were added in sequence under stirring: 60.5 kg of kaolin (solid content of 76% by weight, purchased from Suzhou Kaolin Company), 23.3 kg of aluminum sol (alumina content of 21.5% by weight, provided by Qilu Branch of Sinopec Catalyst Co., Ltd.), 36.1 kg of pseudo-boehmite (solid content of 61% by weight, purchased from Shandong Aluminum Plant) and 7.4 L of hydrochloric acid (HCl content of 31% by weight) and stirred rapidly for 150 minutes. Then, 27 kg (based on NaY dry basis) of unmodified NaY molecular sieve slurry (NaY molecular sieve concentration of 53% by weight, provided by Qilu Branch of Sinopec Catalyst Co., Ltd.) was added and stirred rapidly for 60 minutes. Then, the mixture was spray-dried and calcined in a calcining furnace at 320° C. for 1 hour to obtain catalyst microspheres A1; (2) the catalyst microspheres A1 prepared above were added to 1000 L of decationized aqueous solution and stirred to make them uniformly mixed, 7.87 L of RE(NO3)3 solution (the concentration of the rare earth solution was 330 g / L in terms of RE2O3) was added, stirred, heated to 30° C. and maintained for 1 hour, then filtered and washed, and the filter cake was dried at 120° C. to obtain catalyst microspheres B1 containing rare earth with reduced sodium oxide content, wherein the sodium oxide content of the catalyst microspheres B1 was 1.9% by weight and the RE2O3 content was 2.5% by weight;

[0048] (3) The catalyst microspheres B1 were calcined at 410° C. in an atmosphere containing 45% by volume of water vapor for 6 h, and then dried to reduce the water content to less than 1% by weight to obtain catalyst microspheres C1.

[0049] (4) According to the weight ratio of SiCl4:catalyst microspheres C1 (on a dry basis) = 0.05:1, heated and vaporized SiCl4 gas was introduced, and the reaction was carried out at a temperature of 400°C for 20 minutes. After that, it was washed with 100 L of decationized water and then filtered. The filter cake was dried at 120°C for 5 hours to obtain a finished catalyst SCAT-1. The performance analysis results are shown in Table 1.

[0050] Example 2

[0051] (1) Add 171 kg of decationized water to the catalyst gelling kettle, and then add the gelling raw materials in sequence under stirring: 63.2 kg of kaolin (solid content of 76% by weight, purchased from Suzhou Kaolin Company), 18.6 kg of aluminum sol (alumina content of 21.5% by weight, provided by Qilu Branch of Sinopec Catalyst Co., Ltd.), 37.7 kg of pseudo-boehmite (solid content of 61% by weight, purchased from Shandong Aluminum Plant) and 7.7 L of hydrochloric acid (HCl content of 31% by weight), and stir for 150 minutes. Then add 25 kg (based on NaY dry basis) of unmodified NaY molecular sieve slurry (concentration of 53% by weight, provided by Qilu Branch of Sinopec Catalyst Co., Ltd.) and stir for 60 minutes. Then spray dry and shape, and roast in a roasting furnace at 350° C. for 1 hour to obtain catalyst microspheres A2;

[0052] (2) Add the catalyst microspheres A2 prepared above to 1000 L of decationized aqueous solution and stir to mix evenly, add 6.23 L of RE(NO3)3 solution (the concentration of the rare earth solution is 330 g / L in terms of RE2O3), stir, heat to 40°C and keep for 1 hour, then filter and wash, and dry the filter cake at 120°C to obtain catalyst microspheres B2 containing rare earth with reduced sodium oxide content; the catalyst microspheres B2 contain 2.0% sodium oxide by weight and 2.0% RE2O3 by weight;

[0053] (3) The catalyst microspheres B2 are calcined at 350° C. in an atmosphere containing 55% by volume of water vapor for 6 h, and then dried to reduce the water content to less than 1% by weight to obtain catalyst microspheres C2 containing a molecular sieve with a reduced unit cell constant.

[0054] (4) According to the weight ratio of SiCl4:catalyst microspheres C2 (dry basis) = 0.08:1, heated and vaporized SiCl4 gas was introduced, and the reaction was carried out at a temperature of 300°C for 2 hours. After that, it was washed with 100 L of decationized water and then filtered. The filter cake was dried at 120°C for 5 hours to obtain the finished catalyst SCAT-2. The performance analysis results are shown in Table 1.

[0055] Example 3

[0056] (1) Add 190 kg of decationized water to the catalyst gelling kettle, then add the gelling raw materials in sequence under stirring: 55.3 kg of kaolin (solid content of 76% by weight, purchased from Suzhou Kaolin Company), 18.6 kg of aluminum sol (alumina content of 21.5%, provided by Qilu Branch of Sinopec Catalyst Co., Ltd.), 41 kg of pseudo-boehmite (solid content of 61% by weight, purchased from Shandong Aluminum Plant) and 8.4 L of hydrochloric acid (HCl content of 31% by weight), and stir rapidly for 150 minutes. Then add 29 kg (based on NaY dry basis) of unmodified NaY molecular sieve slurry (concentration of 53% by weight, provided by Qilu Branch of Sinopec Catalyst Co., Ltd.) and stir for 60 minutes. Then spray dry and shape, and roast in a roasting furnace at 300°C for 1 hour to obtain catalyst microspheres A3;

[0057] (2) adding the catalyst microspheres A3 prepared above to 1000 L of decationized aqueous solution and stirring to mix evenly, adding 9.62 L of RE(NO3)3 solution (the concentration of the rare earth solution is 330 g / L in terms of RE2O3), stirring, heating to 35°C and maintaining for 1 h, then filtering and washing, and drying the filter cake at 120°C to obtain catalyst microspheres B3 containing rare earth with reduced sodium oxide content; the sodium oxide content of the catalyst microspheres B3 is 1.8% by weight, and the RE2O3 content is 3.0% by weight;

[0058] (3) The catalyst microspheres B3 are calcined at 390° C. in an atmosphere containing 50% by volume of water vapor and 50% by volume of air for 5 h, and then dried to reduce the water content to less than 1% by weight to obtain catalyst microspheres C3 containing a molecular sieve with a reduced unit cell constant.

[0059] (4) According to the weight ratio of SiCl4:catalyst microspheres C3 (dry basis) = 0.10:1, heated and vaporized SiCl4 gas was introduced, and the reaction was carried out at a temperature of 350°C for 1 hour. After that, it was washed with 100 L of decationized water and then filtered. The filter cake was dried at 120°C for 5 hours to obtain the finished catalyst SCAT-3. The performance analysis results are shown in Table 1.

[0060] Example 4

[0061] The catalyst was prepared by the method of Reference Example 1, except that the pseudo-boehmite was replaced by silica sol in an amount equal to the weight on a dry basis. The resulting catalytic cracking catalyst was designated as SCAT-4.

[0062] Comparative Example 1

[0063] Take 2000 grams of NaY molecular sieve (on a dry basis) and add it to 20 liters of decationized aqueous solution and stir to mix it evenly. Add 580 ml of RE(NO3)3 solution (the concentration of the rare earth solution is 330 g / L in terms of RE2O3), stir, heat to 90-95°C and keep for 1 hour, then filter and wash, dry the filter cake at 120°C, then roast for 5 hours at a temperature of 390°C, in an atmosphere containing 60 volume % water vapor and 40 volume % air, then dry it to make its water content less than 1 weight %, then introduce heated and vaporized SiCl4 gas according to the weight ratio of SiCl4:Y type molecular sieve (on a dry basis) = 0.45:1, react at a temperature of 400°C for 2 hours, then wash it with 20 liters of decationized water, and then filter it to obtain a modified Y type molecular sieve, recorded as DZ1.

[0064] 714.5 g of aluminum sol with an aluminum oxide content of 21% by weight was added to 1565.5 g of decationized water, stirring was started, and 2763 g of kaolin with a solid content of 76% by weight was added and dispersed for 60 minutes. 2049 g of pseudo-boehmite with an aluminum oxide content of 61% by weight was added to 8146 g of decationized water, and 210 ml of hydrochloric acid with a mass concentration of 36% was added under stirring. After acidification for 60 minutes, the dispersed kaolin slurry was added, and then 1500 g (dry basis) of ground DZ1 molecular sieve was added. After stirring evenly, spray drying and washing were carried out, and the catalyst was dried to obtain a catalyst, which was recorded as DC1. The DC1 catalyst obtained contained 30% by weight of DZ1 molecular sieve, 42% by weight of kaolin, 25% by weight of pseudo-boehmite, and 3% by weight of aluminum sol on a dry basis.

[0065] Comparative Example 2

[0066] Take 2000 grams of NaY molecular sieve (on a dry basis) and add it to 25 liters of decationized aqueous solution and stir to mix it evenly. Add 681 ml of RECl3 solution (the solution concentration is 330 g / L based on RE2O3), stir, heat to 90-95°C and keep for 1 hour, then filter and wash. The filter cake is dried at 120°C, and then calcined at a temperature of 440°C in an atmosphere containing 70% by volume of water vapor for 5 hours. After that, it is dried to make its water content less than 1% by weight, and then SiCl4 gas vaporized by heating is introduced according to the weight ratio of SiCl4:Y type zeolite = 0.6:1. At a temperature of 460°C, react for 2 hours, then wash with 20 liters of decationized water, and then filter to obtain modified molecular sieve DZ2.

[0067] Referring to the preparation method of Comparative 1, DZ2 molecular sieve, kaolin, water, pseudo-boehmite binder and aluminum sol are formed into slurry according to the conventional preparation method of catalytic cracking catalyst, spray-dried to prepare microsphere catalyst, and the prepared catalytic cracking catalyst is recorded as DC2. The DC2 catalyst contains 30% by weight of DZ2 molecular sieve, 42% by weight of kaolin, 25% by weight of pseudo-boehmite and 3% by weight of aluminum sol on a dry basis.

[0068] Comparative Example 3

[0069] Take 2000 grams of NaY molecular sieve (dry basis) and add it to 20 liters of decationized aqueous solution and stir to mix it evenly, add 1000 grams of (NH4)2SO4, stir, heat to 90-95°C and keep for 1 hour, then filter and wash, dry the filter cake at 120°C and perform hydrothermal modification, the hydrothermal modification temperature is 650°C, calcine at 100% water vapor for 5 hours, then add it to 20 liters of decationized aqueous solution and stir to mix it evenly, add 193 ml of RE(NO3)3 solution (the concentration of rare earth solution based on RE2O3 is 330 g / L) and 900 g of (NH4)2SO4 were stirred, heated to 90-95°C and maintained for 1 hour, then filtered and washed. The filter cake was dried at 120°C and then subjected to a second hydrothermal modification treatment (temperature 650°C, calcined at 100% water vapor for 5 hours) to obtain a twice ion-exchanged and twice hydrothermally superstable rare earth-containing hydrothermally superstable Y-type molecular sieve, recorded as DZ3.

[0070] DZ3 molecular sieve, kaolin, water, pseudo-boehmite binder and aluminum sol are formed into slurry according to a conventional method for preparing a catalytic cracking catalyst, and spray-dried to prepare a microsphere catalyst. The prepared catalytic cracking catalyst is recorded as DC3 (refer to the preparation method of Comparative Example 1). The DC3 catalyst obtained contains 30% by weight of DZ3 molecular sieve, 42% by weight of kaolin, 25% by weight of pseudo-boehmite and 3% by weight of aluminum sol on a dry basis.

[0071] Comparative Example 4

[0072] The catalyst was prepared according to the method of Example 1, except that the spray-dried shaped product was calcined in a calcining furnace at 500°C for 1 hour. The catalyst was recorded as DC4.

[0073] Comparative Example 5

[0074] The catalyst was prepared by the method of Reference Example 1, except that the calcination atmosphere in step 3 contained 80% by volume of water vapor and the calcination temperature was 550° C. The catalyst was denoted as DC5.

[0075] Embodiments 5 to 8

[0076] Examples 5 to 8 illustrate the catalytic cracking reaction performance of the catalytic cracking catalyst provided by the present invention.

[0077] The catalytic cracking performance of SCAT-1, SCAT-2, SCAT-3 and SCAT-4 catalysts was evaluated in a small fixed fluidized bed reactor (ACE) after aging for 17 hours at 800°C with 100% steam by volume. The cracked gas and product oil were collected and analyzed by gas chromatography. The catalyst loading was 9 g, the reaction temperature was 500°C, and the weight hourly space velocity was 16 h -1 The agent-oil ratio (weight ratio) is 4. The raw material properties of the ACE experiment are shown in Table 2, and the evaluation results are shown in Table 3.

[0078] Comparative Examples 6 to 10

[0079] Comparative Examples 6 to 10 illustrate the catalytic cracking reaction performance of the ultrastable Y-type zeolite prepared by the methods provided in Comparative Examples 1 to 5.

[0080] After aging the DC1-DC5 catalysts at 800°C for 17 hours with 100% steam, their catalytic cracking performance was evaluated in a small fixed fluidized bed reactor (ACE). The evaluation method is shown in Example 4. The raw material properties of the ACE experiment are shown in Table 2. The evaluation results are listed in Table 3.

[0081] Table 1

[0082]

[0083] It can be seen from the results listed in Table 1 that the catalytic cracking catalyst provided by the present invention has a larger pore volume and specific surface area, and at the same time, has better strength, and the sodium oxide content in the catalyst is low, the relative crystallinity of the molecular sieve in the catalyst is high, and the preparation process of the catalyst is free of ammonia nitrogen pollution.

[0084] Table 2 ACE evaluation of crude oil properties

[0085]

[0086] Table 3

[0087] Instance Number Example 1 Example 2 Example 3 Example 4 Sample No. SCAT-1 SCAT-2 SCAT-3 SCAT-4 Agent to oil ratio 4 4 4 4 Product distribution / weight % Dry gas 1.32 1.28 1.34 1.25 Liquefied gas 17.35 17.14 17.23 17.48 Coke 4.52 4.48 4.58 4.18 gasoline 54.12 54.05 54.45 54.62 diesel fuel 16.31 16.81 15.87 16.22 heavy oil 6.38 6.24 6.53 6.25 total 100 100 100 100 Conversion rate / weight% 77.31 76.95 77.6 77.53 Coke selectivity / weight% 5.85 5.82 5.90 5.39

[0088] Table 3 continued

[0089] Instance Number Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Sample No. DC1 DC2 DC3 DC4 DC5 Agent to oil ratio 4 4 4 4 4 Product distribution / weight % Dry gas 1.35 1.41 1.48 1.42 1.39 Liquefied gas 17.05 16.71 14.33 16.25 16.9 Coke 4.9 5.81 8.61 5.11 5.36 gasoline 51.23 50.87 40.91 51.6 52.13 diesel fuel 17.96 18.71 21.25 17.82 17.54 heavy oil 7.51 6.49 13.42 7.8 6.68 total 100 100 100 100 100 Conversion rate / weight% 74.53 74.8 65.33 74.38 75.78 Coke selectivity / weight% 6.57 7.77 13.18 6.87 7.07

[0090] From the results listed in Table 3, it can be seen that the catalytic cracking catalyst provided by the present invention has significantly lower coke selectivity, higher heavy oil conversion activity, and higher gasoline yield. The catalytic cracking catalyst provided by the present invention has a higher heavy oil conversion activity after aging for 17 hours with 100% steam, indicating that it has higher stability.

Claims

1. A method for preparing a catalytic cracking catalyst without ammonia nitrogen pollution, the method comprising mixing a NaY molecular sieve without ion exchange with a binder, clay and water, beating and spray drying, and calcining to obtain catalyst microspheres; then, performing ion exchange modification, moderate hydrothermal ultra-stable modification and SiCl4 gas phase ultra-stable modification treatment; wherein, The preparation method of the catalyst comprises the following steps: (1) Preparation of catalyst microspheres: unmodified NaY molecular sieve is mixed with a binder, clay and water, beaten and spray-dried to form, and calcined at 280-380°C for 1-4 hours to obtain catalyst microspheres A; wherein, on a dry basis, the weight ratio of the binder to the unmodified NaY molecular sieve is 10-45:10-50, and the weight ratio of the clay to the unmodified NaY molecular sieve is 10-80:10-50; the binder is an aluminum-based binder; or the binder is a silicon-based binder and a pseudo-boehmite binder, (2) Ion exchange modification: Catalyst microspheres A are contacted with a rare earth solution to carry out an ion exchange reaction, and then filtered and washed to obtain catalyst microspheres B; (3) Mild hydrothermal ultrastable modification: the catalyst microspheres B are calcined at a temperature of 350-450° C. in an atmosphere containing 40-60% by volume of water vapor for 4-6 hours, and optionally dried to obtain catalyst microspheres C; the water content in the catalyst microspheres C does not exceed 1% by weight; (4) SiCl4 gas phase ultrastable modification: The catalyst microspheres C are contacted with SiCl4 gas at a temperature of 250-450°C for reaction, wherein the weight ratio of SiCl4 to catalyst microspheres C on a dry basis is 0.03-0.2:1, and the reaction time is 10 minutes to 5 hours. The catalyst is then washed, filtered, optionally dried, and optionally calcined to obtain a catalyst product D.

2. The method for preparing a catalytic cracking catalyst according to claim 1, characterized in that: The unmodified NaY molecular sieve described in step (1) refers to the hydrothermally synthesized NaY molecular sieve that is only washed with water and the pH value of the filter cake of the NaY molecular sieve after washing is measured to be 7-9.

3. The method for preparing a catalytic cracking catalyst according to claim 1, characterized in that: The calcination temperature in step (1) is 300-350°C.

4. The method for preparing a catalytic cracking catalyst according to claim 1, characterized in that: The temperature of the rare earth ion exchange modification in step (2) is 20-60° C., the exchange time is 90-120 minutes, and the rare earth solution is an aqueous solution of a rare earth salt.

5. The method for preparing a catalytic cracking catalyst according to claim 1, characterized in that: The calcination temperature in step (3) is 370-420°C.

6. The method for preparing a catalytic cracking catalyst according to claim 1, characterized in that: The atmosphere in step (3) contains 45-55% by volume of water vapor.

7. The method for preparing a catalytic cracking catalyst according to claim 1, characterized in that: The calcination time in step (3) is 5 to 6 hours.

8. The method for preparing a catalytic cracking catalyst according to claim 1, characterized in that: The temperature of the contact reaction between the catalyst microspheres C and the SiCl4 gas in step (4) is 280-420°C.

9. The method for preparing a catalytic cracking catalyst according to claim 1, characterized in that: The time for the catalyst microspheres C to contact and react with SiCl4 gas in step (4) is 0.5 to 2 hours.

10. The method for preparing a catalytic cracking catalyst according to claim 1, characterized in that: In step (4), the weight ratio of SiCl4 to catalyst microspheres C is 0.05-0.15:

1.

11. The method for preparing a catalytic cracking catalyst according to claim 1, characterized in that: The washing method described in step (4) is washing with water, and the washing conditions are catalyst: H2O = 1:8~12 weight ratio, pH value is 3~4, and washing temperature is 20~50°C.

12. The method for preparing a catalytic cracking catalyst according to claim 1, characterized in that: The binder is a silicon-based binder and a pseudo-boehmite binder. The silicon-based binder is silica sol, and the weight ratio of silica sol to unmodified NaY molecular sieve on a dry basis is 5-45:10-50; it also contains pseudo-boehmite binder, and the weight ratio of pseudo-boehmite binder on a dry basis to silica sol on a dry basis is 0.1-1:1; or, The aluminum-based binder is one or more of aluminum sol, pseudo-boehmite, and aluminum gel, and the content of the aluminum-based binder in the catalyst microspheres A is 10-40% by weight on a dry basis; On a dry basis, the weight ratio of the aluminum-based binder to the unmodified NaY molecular sieve is 10-40:10-50.

13. The method for preparing a catalytic cracking catalyst according to claim 2, characterized in that: The pH value of the filter cake is 7-8, and the water is industrial water.

14. The method for preparing a catalytic cracking catalyst according to claim 4, characterized in that: The temperature of the rare earth ion exchange modification in step (2) is 25-45° C.; the rare earth salt is rare earth chloride and / or rare earth nitrate.

15. The catalytic cracking catalyst obtained by the catalytic cracking catalyst preparation method according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Preparation method of cracking catalyst

    CN101670295A

  • Rare earth-containing Y-type molecular sieve cracking catalyst and preparation method thereof

    CN102806096A

  • Cracking catalyst and preparing process thereof

    CN1098130A

  • Preparation of high-silica faujasite

    US3639099A

  • Preparation of high silica synthetic faujasite

    US3671191A